The new Earth from above : 365 days - Arthus-Bertrand, Yann (Abrams, 2009)
A four page statistical introduction, "The Earth In Figures," is followed by 365 full-page spreads, from January 01 through December 31, featuring aerial photographs of the earth's surface accompanied by a descriptive paragraph, with an emphasis on ecology and the impact of human culture on the Earth. A brief essay precedes each month's photographs.